FACTORS AFFECTING CUSTOMER SATISFACTION THROUGH PURCHASE DECISION AS AN INTERVENING VARIABLE (case study on PT. Kereta Api Indonesia Daop 4 Semarang) - Dhelpia, Fhila; Bachtiar, M. Rifki (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of product quality, brand image, and promotion on customer satisfaction, both directly and indirectly through purchase decisions as a mediating variable, among users of railway transportation services in Semarang City. A quantitative approach was employed, using regression analysis and mediation testing through the Sobel test. The results indicate that brand image and promotion have a positive and significant effect on both purchase decisions and customer satisfaction. In contrast, product quality does not have a significant effect on either purchase decisions or customer satisfaction. Purchase decisions are proven to significantly mediate the relationship between brand image and promotion on customer satisfaction but do not mediate the effect of product quality on customer satisfaction. These findings suggest that positive perceptions of brand image and effective promotional strategies are key factors in driving purchase decisions and enhancing customer satisfaction in the railway transportation sector. This study provides strategic implications for PT KAI in designing more customer-oriented marketing and service approaches.